Multiple Intelligences, Key Competences and STREAMS: A Project and Dialogue Based Approach through Flexible Integration - Escamilla, Amparo; Grandal, María del Mar; Randell, David (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2021)
Quality innovation requires a constant search for accuracy, systematicity, agreements and cooperation of all parties involved: educators, management, pupils and the educational community. It is demanded a willingness to improve and be open to new ideas and opportunities with strong leadership. The essence of effective change is research and rigor. It is worth to keep on working with current methodological initiatives that have proved to be contrasted and useful. Yet they have to reach their full potential by widening their scope and delving into their achievements. In this way, new teaching frameworks, techniques, resources and organizational systems must be explored not only through the Multiple Intelligences and Key Competencies based projects, but also through new approaches like STREAMS.Key words: Multiple Intelligences, Key Competences, STEM, STREAMS, thinking strategies, projects
Keywords: Multiple Intelligences; Key Competences; STEM; STREAMS; thinking strategies; projects